Continuous Dynamic Monitoring of Lively Footbridges - E. Caetano (2016)
The paper describes two dynamic monitoring systems installed in lively footbridges with the purpose of characterizing the dynamic behavior and response of these structures and possibly detecting damage at early stages. Some monitoring results illustrate the capabilities of the presently existing technology.